Nanoencapsulation of Achyrocline satureioides (Lam) DC—Essential Oil and Controlled Release: Experiments and Modeling - Caroline G. F. da Silva; Rafaela R. Petró; Jéssica H. de Castro; Rafael N. Almeida; Eduardo Cassel; Rubem M. F. Vargas (Pharmaceutics)
Background/Objectives: Degradation by physical and chemical agents affects the properties of essential oils; therefore, this study aimed to protect the volatile compounds present in essential oils through biopolymer encapsulation. Methods: The Achyrocline satureioides (Lam) DC. essential oil was obtained by steam distillation at 2.5 bar. The nano-sized physical coating of the active oil core resulted in an optimal polymer/oil ratio of 1:3 and particle diameter of 178 nm. The particle morphology was evaluated using scanning electron microscopy and transmission electron microscopy. The inclusion of the essential oil in the polymer was confirmed using thermogravimetric analysis. Results: The pH of the formulation remained stable for 90 days, and controlled release and encapsulation efficiencies were evaluated. Formulations were evaluated using the perfumery radar technique, which indicated a predominantly woody profile. The diffusion of fragrant compounds in the air was assessed over time and mathematically modeled. Conclusions: The produced nanostructures were efficient for the controlled release of volatile compounds from the essential oil of Achyrocline satureioides.